The Spanish Social Security : Prospects of the Pension and Health-Care Systems - Levy, Joaquim (Washington, D.C. : International Monetary Fund, 1995)
The social security system in Spain has steadily expanded since the late 1970s. Currently, social security expenditure exceeds 15 percent of GDP, being a factor of fiscal imbalance. This paper reviews achievements and the current situation of the social security system, discusses changes in the financing of health-care expenditure in view of the need for fiscal consolidation by the general government, and analyzes the scope for a partial prefunding of future liabilities of the pension system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet